Binding Assays for Bromodomain Proteins: Their Utility in Drug Discovery in Oncology and Inflammatory Disease. Issue 1 (2nd April 2018) - Zolotarjova, Nina I.; Wynn, Richard
Abstract: Bromodomains are protein domains that recognize acetylated lysine residues and are important for recruiting a large number of protein and multiprotein complexes to sites of lysine acetylation. They play an important role in chromatin biology and are popular targets for drug discovery. Compound screening in this area requires the use of biochemical assays to assess the binding potency of potential drug candidates. Foremost among the efforts to target bromodomains are those aimed at identifying compounds that interact with the bromodomain and extra‐terminal domain (BET) family of bromodomain‐containing proteins (BRD2, BRD3, BRD4, and BRDT). Inhibitors of these proteins are under clinical development for a large variety of oncologic indications. Described in this unit are several assays to assess the binding potency and selectivity within the BET protein family. Included are AlphaScreen, fluorescence polarization, and thermal shift assays. The strengths and weaknesses of each assay are discussed. © 2018 by John Wiley & Sons, Inc.